(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores effective methods for developing reading skills in learners across various age groups and proficiency levels. It outlines strategies such as phonemic awareness, extensive reading, guided reading, vocabulary enrichment, and the use of digital tools. Emphasis is placed on both cognitive and metacognitive strategies to foster independent, lifelong reading habits. The article is useful for educators, language learners, and curriculum developers.